Near-infrared photothermal conversion properties of carbazole-based cocrystals with different degrees of charge transfer - Shi, Pan; Liu, Xiao-Xu; Dai, Xia-Lin; Lu, Tong-Bu; Chen, Jia-Mei (CrystEngComm, 2022)
Charge transfer cocrystals offer an opportunity to construct high performance organic photothermal materials. However, it is still challenging to modulate the degree of charge transfer of cocrystals to achieve rationally designed photothermal functional materials. Herein three charge transfer cocrystals composed of carbazole (CZ)/3,6-dichlorocarbazole (ClCZ)/3,6-dibromocarbazole (BrCZ) as -donors (D) and 7,7′,8,8′-tetracyanoquinodimethane (TCNQ) as a π-acceptor (A), namely CZ/TCNQ , ClCZ/TCNQ and BrCZ/TCNQ , were obtained and subjected to spectroscopic and photothermal conversion studies as well as density functional theory calculations. The crystal structures reveal that the donor and acceptor molecules of each cocrystal adopt a DADADA mixed stack structure. With steric hindrance and electron withdrawing effects of chlorine/bromine atoms on carbazole, the charge transfer degree of CZ/TCNQ is reduced from 0.25 to 0.07 for ClCZ/TCNQ and 0.03 for BrCZ/TCNQ . The three cocrystals display broad absorption over the 300 to 900 nm range without significant photon emission. The near-infrared photothermal conversion efficiency reaches 53.7% ( CZ/TCNQ ), 48.5% ( ClCZ/TCNQ ) and 32.0% ( BrCZ/TCNQ ), respectively. These cocrystals have narrowed HOMO-LUMO gaps, which is attributed to the strong charge transfer transition and agrees with the photophysical and photothermal conversion properties of the cocrystals. This study demonstrates that the modulation of the charge transfer degree by intelligent design of donor-acceptor pairs can be an effective means to regulate the photothermal conversion efficiency of charge transfer cocrystals. Finally, CZ/TCNQ was successfully applied as an appealing photothermal material in photothermal imaging and functional electrical device control. Three charge transfer carbazole-based cocrystals were obtained and demonstrated regulated photothermal conversion efficiency by the modulation of the charge transfer degree via intelligent design of donor-acceptor pairs.